Occurrence of South American Tomato Leaf Miner (Tuta absoluta) and Current Management Practices Adopted by Farmers in Lalitpur District, Nepal - Lamsal, Aasha; Sah, Lalit P.; Giri, Ajay P.; Devkota, Mukti; Colavito, Luke A.; Norton, George; Rajotte, Edwin George; Muniappan, Rangaswamy (Journal of the Plant Protection Society, 2018)
A study was carried out to document occurrence of Tuta absoluta and current management practices adopted by farmers in Lalitpur district (Lele VDC) where a total of 70 respondents were interviewed using random sampling method. The study comprises three target groups viz. structured questionnaire survey of farmers growing tomatoes (50); structured questionnaire survey of traders involved in tomato business (10); and lastly farmers’ field survey to determine the extent of Tuta absoluta damage in leaves (10). The results revealed in the field Tuta absoluta is the most devastating insect pest and has done the highest 72% losses in the farmer field which is the heavy loss for the farmers and as a result, production of tomato has decreased in 2016 as compared to 2015. However while all the respondents claimed to have faced pest problem only 20% of the respondents were aware about Tuta absoluta. The survey also showed that 70% of the respondents were using para-pheromone lure (TLM lure) while 10% were using para-pheromone lure + light trap, 60% were using botanicals and bio-pesticides like Neem, Bacillus Thuriengensis in alternative ways and 20% were using chemicals like Chlorantraniliprole 18.5% SC (Alcora), Botanical pesticides (Dadaguard), Emamectin benzoate (EMAR 5% WDC), Cyromazine 10% SC (King hunter), Flubendiamide 39.35% SC (FAME 480 SC) without considering their environmental and health risks. All recommended Tuta absoluta control strategies such as pheromone trapping for monitoring as well as suppression, chemical and biological control were not available or known by growers. Trader’s survey showed on an average of 11.7 percent of fruits damage in market where as in farmers field survey revealed an average of 3 percent loss in net house and 10.3 percent loss in open field.